Progressive delamination analysis through two-way global-local coupling approach preserving energy dissipation for single-mode and mixed-mode loading. (1st September 2019) - Akterskaia, Margarita; Camanho, Pedro P.; Jansen, Eelco; Arteiro, Albertino; Rolfes, Raimund
Abstract: Together with fiber breakage and matrix cracking, delamination is one of the common damage mechanisms occurring in laminated fiber-reinforced composite structures. Delamination initiates due to the relatively low interlaminar strength of adjacent plies. Delamination onset and propagation can be induced by various combinations of loads and usually leads to a significant reduction of the load-carrying capacity of the structure. For this reason, an efficient and reliable progressive failure analysis capability is required. In this work, the delamination process is simulated by means of a two-way global-local coupling approach. In particular, within this novel global-local approach a method is introduced that ensures the preservation of the dissipated energy when switching between the global and local level. This approach is tested and illustrated under single-mode I and II, and mixed-mode loading in the double cantilever beam (DCB), the end-notched flexure (ENF) and the mixed-mode bending (MMB) benchmark tests, respectively, and the results are compared to available analytical solutions. Finally, the developed method has been applied to a one-stringer stiffened panel and a good agreement was attained compared to the solid model reference solution.